2005
DOI: 10.1158/1078-0432.ccr-05-0661
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Loss of PMS2 Expression in Colorectal Cancers: Frequency, Patient Age, and Familial Aggregation

Abstract: Purpose: Most colorectal cancers that have high levels of microsatellite instability (MSI-H) show loss of immunohistochemical expression of proteins that participate in the DNA mismatch repair process, most often involving MLH1 and MSH2. Less commonly, a third DNA mismatch repair protein, MSH6, may also be lost as the primary event. Rarely, tumors with MSI-H show normal expression of these three proteins.The genetic deficiency leading to the MSI-H phenotype in such cases is unknown. PMS2 is another member of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 32 publications
(16 reference statements)
3
43
0
3
Order By: Relevance
“…Thus, general population screening recommendations for colon cancer surveillance beginning at age 50 would not be sufficient for families with a PMS2 gene mutation. However, the standard LS cancer screening guidelines (colonoscopy every 1-2 years beginning at age [20][21][22][23][24][25] 47 for carriers of MLH1 or MSH2 mutations may be extreme given the lower penetrance. Our data suggest that PMS2 mutation carriers should probably follow an intermediate screening regimen such as beginning colonoscopy every 1-2 years at 30, as was recommended by Lindor et al for individuals with MSH6 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, general population screening recommendations for colon cancer surveillance beginning at age 50 would not be sufficient for families with a PMS2 gene mutation. However, the standard LS cancer screening guidelines (colonoscopy every 1-2 years beginning at age [20][21][22][23][24][25] 47 for carriers of MLH1 or MSH2 mutations may be extreme given the lower penetrance. Our data suggest that PMS2 mutation carriers should probably follow an intermediate screening regimen such as beginning colonoscopy every 1-2 years at 30, as was recommended by Lindor et al for individuals with MSH6 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…22 IHC showing isolated loss of PMS2 protein is suggestive of a germline PMS2 mutation. Two large studies have shown that loss of PMS2 protein and retention of MLH1, MSH2, and MSH6 mismatch repair proteins occurs in 4.3% of colorectal tumors exhibiting a high degree of microsatellite instability (95% CI 2.7% -6.4%), 23 and 11.5% of colorectal tumors with abnormal mismatch repair IHC (95% CI 6.7% -18.0%). 24 Baudhuin et al found loss of PMS2 protein in <1% of colorectal tumors with abnormal IHC from cases unselected for family history of cancer and 4% of colorectal tumors with abnormal IHC that were classified as "moderate to high risk patients" based on "being referred for routine clinical molecular testing for Lynch syndrome at the Mayo Clinic."…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry was performed according to previously described and standard protocols. 16,27 Germline …”
Section: Microsatellite Instability Immunohistochemistry and Germlinementioning
confidence: 99%
“…17,18 These findings were similar to the findings of this study. Similarly, Gill et al 19 showed that the majority of MSI-H colon cancers (499 of 535, 93%) had loss of expression for at least one of the proteins for MLH1, MSH2, and/or MSH6. However, the selective loss of PMS2 (with normal expression of MLH1, MSH2, and/or MSH6) was detected in 4.3% (23 of 529) of all MSI-H colon cancer.…”
mentioning
confidence: 89%
“…However, the selective loss of PMS2 (with normal expression of MLH1, MSH2, and/or MSH6) was detected in 4.3% (23 of 529) of all MSI-H colon cancer. 19 According to Gill et al 19 , PMS2 negative cancer occurs mostly in males (64%) aged 28-67 years and is more common in the right colon (52%). In our study, PMS2 negative colon cancers were more common in males (75%) aged 29-83 years as well.…”
mentioning
confidence: 99%